Production of plastic lubricants on the basis of waste lubricated oils - Grigorov, Andrey; Zelenskii, Oleg; Saienko, Leonid; Zhyrnova, Svitlana (My University, 2019)
The results of studies of used lubricating oils, various functional purposes and greases obtained on their use as a thickener 5 wt % of secondary low-pressure polyethylene have been presented. Depending on the operating conditions in the samples of waste oils, the content of water and mecha-nical impurities varies in the range of 0.03-0.3 wt %, 0.08-1.30 wt %. Heating the oils to a temperature of 230°C showed that in the area of heating to a temperature of 200°C, the mass loss and decrease in viscosity are not significant, however, if this temperature is exceeded, an intensive process of destruction of oil hydrocarbons begins, and it will negatively affect the quantitative yield and perfor-mance properties of the lubricant. The obtained results showed that the lower the viscosity of the base oil from which the grease is made, the less stable it is during storage and operation, the worse its adhesive properties. Waste motor and transmission gear oils are advisable to use in the production of antifriction greases while hydraulic and industrial plastic lubricants are better to use in the production of protective greases.
Keywords: plastic grease; thickener; polyethylene products; base oil; quality indicators